1987
DOI: 10.1128/jb.169.8.3608-3616.1987
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic initiation of differentiation and secondary metabolism by Streptomyces griseus: significance of the stringent response (ppGpp) and GTP content in relation to A factor

Abstract: I investigated the significance of the intracellular accumulation of guanosine 5'-diphosphate 3'-diphosphate (ppGpp) and of the coordinated decrease in the GTP pool for initiating morphological and physiological differentiation of Streptomyces griseus, a streptomycin-producing strain. In solid cultures, aerial mycelium formation was severely suppressed by the presence of excess nutrients. However, decoyinine, a specific inhibitor of GMP synthetase, enabled the cells to develop aerial mycelia in the suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
223
2
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(234 citation statements)
references
References 32 publications
(33 reference statements)
7
223
2
1
Order By: Relevance
“…GYM medium was described previously. 16 Scandium chloride hexahydrate (ScCl 3 Á6H 2 O; purity, 99.9%) and lanthanum chloride heptahydrate (LaCl 3 Á7H 2 O; purity, 99.9%), together with other rare earths (all chloride-salts; purity, 497%) were purchased from Wako Pure Chemical (Osaka, Japan). These rare earths were added to the autoclaved agar medium after cooling to 50-60 1C.…”
Section: Methodsmentioning
confidence: 99%
“…GYM medium was described previously. 16 Scandium chloride hexahydrate (ScCl 3 Á6H 2 O; purity, 99.9%) and lanthanum chloride heptahydrate (LaCl 3 Á7H 2 O; purity, 99.9%), together with other rare earths (all chloride-salts; purity, 497%) were purchased from Wako Pure Chemical (Osaka, Japan). These rare earths were added to the autoclaved agar medium after cooling to 50-60 1C.…”
Section: Methodsmentioning
confidence: 99%
“…Some Streptomyces strains produce SS but the SS are produced by fragmentation of mycelia (Figure 5b). [17][18][19][20][21][22][23] Feeding and shift-down experiments were carried out to identify the physiological regulation of SS formation of the strain KM-6054 T using minimum medium (MM) and casamino acid. 24 In feeding experiments, the strain produced SS when casamino acids were added in MM within 4 h after inoculation, but not when added after 6 h. In a nutritional shift-down experiment, SS were formed when casamino acids were removed from MM-CA after 8 h cultivation, but not when removed within 6 h. SS formation may therefore require at least 8 h incubation under nutrient-rich conditions.…”
Section: Characteristics Of Aerial and Submerged Spores Ofmentioning
confidence: 99%
“…Although reports about spores formed in the submerged culture are few, cases of Streptomyces griseus, 16,[21][22][23][24][25] Streptomyces roseosporus, 20 Streptomyces acrimycini, 18 Streptomyces albus 18 and Streptomyces venezuelae 19 have been published. Among them, Ochi et al 22,23 reported that the strain of S. griseus IFO 13189 forms SS along with a stringent response to nutritional starvation.…”
Section: Characteristics Of Aerial and Submerged Spores Ofmentioning
confidence: 99%
“…Spontaneous streptomycin-resistant mutants were obtained as colonies that grew within 5-7 days after spores were spread on glucose-yeast extract-malt extract (GYM) agar 11 containing various concentrations of streptomycin. Mutations in rpsL or rsmG genes were determined by DNA sequencing using the primers listed in Table 1.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Mutations in rpsL or rsmG genes were determined by DNA sequencing using the primers listed in Table 1. Cultivation was performed at 30 1C (for preculture) or 25 1C (for main culture) using SPY medium 11 with rotary shaking at 220 r.p.m.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%